The Dynamics of Market Efficiency - Rösch, Dominik M.; Subrahmanyam, Avanidhar; Dijk, Mathijs A. van (Review of Financial Studies, 2017)
We study the dynamics of high-frequency market efficiency measures. We provide evidence that these measures comove across stocks and with each other, suggesting the existence of a systematic market efficiency component. In vector autoregressions, we show that shocks to funding liquidity (the TED spread), hedge fund assets under management, and a proxy for algorithmic trading are significantly associated with systematic market efficiency. Thus, stock market efficiency is prone to systematic fluctuations, and, consistent with recent theories, events and policies that impact funding liquidity can affect the aggregate degree of price efficiency.